Answer:
(y-12)/4
Step-by-step explanation:
If g(x) is the inverse of f(x)
and f(x) = 4x + 12
f⁻¹(x) = g(x)
let f(x) be represented as y
f(x)
= y
y = 4x + 12
subtract 12 from both sides
y-12= 4x
divide both sides by 4
(y-12)/4 = x
so f ⁻¹ (y)= (y-12)/4 so g(x) = (x-12)/4
Answer:False
Step-by-step explanation:#UwU God
Try the first option if that's an option
Answer:
y= -4 x+3
Step-by-step explanation: A(1, -1)
the equation is y - y (A)=m*( x-x(A) )
y-(-1)=-4(x-1)
y+1=-4x+4
y= -4x+4-1
y=-4x+3
y=-4x+4-1